The lowering days : a novel - Brown, Gregory (Novelist) (Harper, an imprint of HarperCollinsPublishers, 2021)
"David Almerin Ames and his brothers, Link and Simon, believed the wild patch of Maine where they lived along the Penobscot River belonged to them. Their affinity for the natural world derives from their parents: Arnoux, a romantic artist and Vietnam War deserter who builds boats by hand, and Falon, an activist journalist who runs The Lowering Days, a community newspaper which gives equal voice to indigenous and white issues. Then a bankrupt paper mill, once the Penobscot Valley's largest employer, is burned to the ground on the eve of reopening. Falon receives a letter from a Penobscot Nation teenager confessing to the crime - an act of justice for a sacred river under centuries of assault from toxic waste. The divide within the community widens, ending in a cycle of violence."--Publisher.